TINGKAT KEBERHASILAN PEMIJAHAN IKAN KAPIAT (Puntius schwanenfeldi Blkr) DENGAN INJEKSI HORMON BERBEDA - Wiwien Febrian; Santi Mayasari; Catur Setiowibowo; Sofian Sofian (Jurnal Perikanan Darat dan Pesisir (JPDP), 2020)
Fish reproduction information of tinfoil barb (Puntius schwanenfeldi) in captivity is little known, therefore, it is necessary to have a basic study on the spawning of fish with hormonal stimulation. The purpose of this study was to evaluate the combination of ovaprim and spawnprim hormones on the reproductive performance of tinfoil barb (P. schwanenfeldi). The doses of hormones tested for fish spawning were 0.5 ml / kg of ovaprim and 1 ml / kg of spawnprim. The results showed that the combination hormonal stimulation between ovaprim and spawnprim showed a good response, namely spawning occurred in all tested broodstock. The highest fecundity was 106,524 with a gonad weight of 44 grams. Meanwhile, the highest somatic gonad index (GSI) value of kapiat was 14.37%).